A randomized phase II study of bone-targeted therapy containing strontium-89 in advanced castrate-sensitive prostate cancer - Bilen, Mehmet Asim (Cancer, 2014)
BACKGROUND: Use of radiopharmaceutical may improve the survival time of patients with castrate-resistant prostate cancer and bone metastases. Whether androgen-deprivation therapy (ADT) combined with bone-targeted therapy provides clinical benefit for patients with advanced castrate-sensitive prostate cancer has not been investigated. METHODS: A total of 80 male patients were enrolled, of whom 79 were randomized: 40 to the control arm and 39 to the Sr-89 arm. After randomization, patients in both study arms received ADT, doxorubicin, and zoledronic acid. Kaplan-Meier methodology was used to evaluate progression-free survival (PFS) time. Multivariate Cox proportional hazards regression was used to evaluate the effects of Sr-89 after controlling for the number of bone metastases. RESULTS: Median follow-up time for the 29 patients alive at the last follow-up was 76.9 (range: 0.07 – 103.4) months. Median PFSs were 18.5 months (95% CI: (9.7, 49.4)) in the control arm and 12.9 months (95% CI: (8.9, 72.5)) in the Sr-89 arm (p = 0.86). No patient developed myelodysplastic syndrome or hematologic malignancy. Unplanned subgroup analysis suggested increased efficacy of bone-targeted therapy for greater extent of bone involvement (ie, >6 vs 6 bone metastases on the bone scan). CONCLUSIONS: Our data showed that bone-targeted therapy using one dose of Sr-89 combined with chemohormonal ablative therapy did not favorably impact the PFS of patients with castrate-sensitive prostate cancer. The combined therapy was feasible and safe. Whether such bone-targeted therapy provides a favorable outcome for those patients with greater tumor burden in the bone warrants further investigation.